Reduced contact time of a droplet impacting on a moving superhydrophobic surface - Zhang, Xuan (2021)
While the droplet impact dynamics on stationary superhydrophobic surfaces has been extensively studied, the dynamic behaviors of impact droplets on moving superhydrophobic surfaces have received less attention. Here, we report the droplet impact dynamics on a moving superhydrophobic surface. We show that compared to the stationary surface, the moving superhydrophobic surface breaks the symmetry in both droplet spreading and retracting. Specifically, the shear force exerted by the moving surface acting on the impact droplet enlarges the maximum spreading in the moving direction, and thus, the droplet contact time is reduced. The contact time of impact droplets was examined thoroughly under the effects of the droplet impact (normal) and the wall moving (tangential) Weber numbers. We provide a scaling analysis to explain how the contact time depends on the normal and tangential Weber numbers. Our experimental investigation and theoretical analysis provide insight into the droplet impact dynamics on moving superhydrophobic surfaces.